Military Intervention by Consent and Its Relationship to International Human Rights Law. (2017) - Horowitz, Jonathan
Abstract : These remarks focus on the issue of "military intervention by consent" from the perspective of international human rights law (IHRL). More specifically, they focus on how the consenting state's human rights obligations can impact what that state can, and cannot, consent to.